2017
DOI: 10.11648/j.bio.20170506.14
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Damage Caused by Wastewater Discharge into the Lake Manzala in Egypt

Abstract: Lake Manzala is a brackish lake in northeastern Egypt on the Nile Delta. It is the largest of the northern Delta lakes of Egypt. The Lake is exposed to high inputs of pollutants from industrial, domestic, and agricultural sources. Climate gases and large amounts of particulate matter, nutrients, bacteria, heavy metals, and toxic organics are transported to the Lake through the wastewater discharge. Water samples were collected and subjected to physicochemical analysis and microbiological study. Results have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 7 publications
3
26
3
Order By: Relevance
“…Heavy metals are especially toxic due to their ability to bind with proteins and prevent DNA replication [3]. The lake has been gradually transformed from a largely marine or estuarine environment to a eutrophic nearly fresh water system which can have significant negative ecological, health, social and economic impacts on human [4]. These result in poor water quality and reduction in the lake productivity of fish [5].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are especially toxic due to their ability to bind with proteins and prevent DNA replication [3]. The lake has been gradually transformed from a largely marine or estuarine environment to a eutrophic nearly fresh water system which can have significant negative ecological, health, social and economic impacts on human [4]. These result in poor water quality and reduction in the lake productivity of fish [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Lake is exposed to high inputs of pollutants from industrial, domestic, and agricultural sources. Climate gases and large amounts of particulate matter, nutrients, bacteria, heavy metals, and toxic organics are transported to the Lake through the wastewater discharge (Ismail and Hettiarachchi, 2017). The Lake received about 7500 million cubic meters of untreated industrial, domestic and agricultural drainage water, discharged annually through six main drains; Bahr El-Baqer Drain, Hadous Drain, Ramsis Drain, El-Serw Drain, Matariya Drain and Faraskour Drain.…”
Section: Introductionmentioning
confidence: 99%
“…The Lake received about 7500 million cubic meters of untreated industrial, domestic and agricultural drainage water, discharged annually through six main drains; Bahr El-Baqer Drain, Hadous Drain, Ramsis Drain, El-Serw Drain, Matariya Drain and Faraskour Drain. This amount of wastewater was reduced to about 4000 million cubic meters after construction of El-Salam Canal (Abdel-Baky et al, 1998;El-Ghazali et al, 2015;Ismail and Hettiarachchi, 2017). The drains convey large amount of nutrients, especially from Bahr-El-Bakar, Ramsis and Hadous drains that are heavily contaminated by sewage and industrial wastewater (El-Ghazali et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This outlet allows an exchange of water between the Lake and the Mediterranean Sea. This makes the Northern portion of Lake to be characterized by high salinity [8]. El-Moselhy and Gabal [9] found that the highest values of metals were observed at stations influenced by various pollution sources such as harbours sewage and industrial drains.…”
Section: Introductionmentioning
confidence: 99%